2021
DOI: 10.1097/qad.0000000000003012
|View full text |Cite
|
Sign up to set email alerts
|

Can HIV epidemics among MSM be eliminated through participation in preexposure prophylaxis rollouts?

Abstract: To study the conditions under which PrEP coverage can eliminate HIV among men who have sex with men (MSM) in the Paris region.Design: Mathematical modeling. Methods:We propose an innovative approach, combining a transmission model with a game-theoretic model, for decision-making about PrEP use. Individuals at high risk of HIV infection decide to use PrEP, depending on their perceived risk of infection and the relative cost of using PrEP versus antiretroviral treatment (ART), which includes monetary and/or non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Among the latter, 4 are in the transition zone. Europe is in the high-efficacy region, in accordance with previous studies recommending risk-based distribution 5 , 37 . Notably, many communities in areas of active PrEP roll-out 38 are in the low-efficacy region: it is the case of Brazil and of those in southern Africa (excluding Botswana).…”
Section: Resultssupporting
confidence: 84%
“…Among the latter, 4 are in the transition zone. Europe is in the high-efficacy region, in accordance with previous studies recommending risk-based distribution 5 , 37 . Notably, many communities in areas of active PrEP roll-out 38 are in the low-efficacy region: it is the case of Brazil and of those in southern Africa (excluding Botswana).…”
Section: Resultssupporting
confidence: 84%
“…Even if risk compensation is 100% (all users stop using condoms), our modelling results still showed that such a decrease in condom use among those who use PrEP (which acts like a molecular condom) would, in fact, have a negligible effect on HIV epidemic control (Table 2A for stochastic modelling, and Table 4 for deterministic modelling). Jijón et al ( 2021) also reported similar results, indicating that risk compensation with none of the PrEP users using condom only minimally increase the PrEP coverage rate required for elimination 25 . Likewise, our study further revealed that the other two often-raised concerns for PrEP, imperfect (75%) adherence and occasional (1%) drug resistance, do not have a meaningful impact on the effect of a high-coverage PrEP program in eliminating the HIV epidemic among MSM.…”
Section: Discussionmentioning
confidence: 88%
“…Rapid, targeted, high-coverage roll-out of PrEP was associated with a rapid decline in new HIV diagnoses in New South Wales, Australia 23 . Modeling studies suggested that HIV elimination might be possible in the Netherlands and the Paris region with PrEP coverage rates of 82% and 55%, respectively 24,25 . However, the necessity, impact on achieving the WHO's goal to end the AIDS epidemic by 2030, and costeffectiveness of implementing a high-coverage PrEP program for HIV elimination have not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, decisions made by individuals, within a given epidemiological context, have been typically described using mixed models, merging a game-theoretic model and an epidemic model [40,51,52]. Several topics have been addressed thus far: voluntary vaccination [42,50,[53][54][55][56][57][58][59][60][61][62][63][64], adoption of pre-exposure prophylaxis [65], social distancing [66][67][68] and self-isolation [69]. In fact, Hellmann and Thiele [69] modeled home testing as an aid in the decision making about whether or not to self-isolate.…”
Section: Introductionmentioning
confidence: 99%